Differential characteristics and source contribution of water pollutants before and after the extreme rainfall event in the Huaihe River Basin - Zhang, Yan; Zou, Lei; Li, Ping; Du, Zhenjie; Dou, Ming; Huang, Zhongdong; Liang, Zhijie; Qi, Xuebin (Frontiers in Environmental Science, 2022)
Various pollutants are collected into rivers through runoff when rainstorms occur, which can harm the aquatic ecological environment, therefore, strengthening the analysis of river pollution sources before and after rainstorms can reduce the impact of rainstorm runoff periods in regard to the risk from river water pollutants. In this study, the water pollutant differential characteristics and pollution source identification in the Henan section in the Huaihe River Basin were explored before and after the extreme rainfall event, and the monitoring data for nine water quality indicators in the monitoring sections were selected. The changing and differential characteristics and processes of the water quality indicators in the Huaihe River Basin before and after the rainstorm were analyzed by using statistical analytical methods and the comprehensive water quality identification index (IWq), and the absolute contribution rates of pollution sources were calculated by the absolute principal components-multiple linear regression model (APCS-MLR). The results showed that the values of pH, DO (Dissolved oxygen) and EC (Electrical conductance) after the rainstorm were lower than those before the rainstorm, while the turbidity, CODMn (Permanganate index), NH3−N (Ammonia nitrogen), TP (Total phosphorus) and TN (Total nitrogen) increased after the rainstorm. The correlations between pH and DO and other water quality indicators increased after the rainstorm, while the correlations between WT (Water temperature), turbidity, CODMn, NH3−N, TP and TN decreased significantly after the rainstorm. The water pollution of each monitoring section increased after the rainstorm; for example, the water quality conditions at Zhoukou Kangdian (ZKKD), Xihua Zhifang (XHZF) and Suixian Banqiao (SXBQ) increased by 42.11%, 36.84% and 25.73% to Class V of the environmental quality standards for surface water in China, respectively. The absolute contribution rates of the PC1 to CODMn and TP were 33.86% and 41.11% before the rainstorm, respectively. The absolute contribution rates of the PC2 to DO and TN were 50.77% and 60.26% after the rainstorm, respectively.